Evolutionary and phylogenic relationships of wild and crop species of Iranian Saffron by DNA barcoding - Golshani, Farshid; Fakheri, Brat Ali; Solouki, Mahmood; Mahdinezhad, Nafiseh; Feriz, Majid Reza Kiani (Bangladesh Journal of Botany, 2020)
DNA barcoding method was applied to identify and study the phylogenic relationships existing between 13 species of saffron collected in Iran including 4 crop and 9 wild species. PCR amplifications were performed using primers designed on the nucleotide sequence of three plastid barcode genes, comprising two protein encoding genes (rbcL and matK) and an intragenic spacer (trnH-psbA), and a nuclear region (ITS). A total of 52 sequences were obtained and registered in NCBI database. In particular, 21 of these sequences were not present in the scientific library. Nucleotide polymoprhic sites were counted for each barcode gene (rbcL, n = 16; matK, n = 15; trnH-psbA, n = 46; ITS, n = 71). Each sample could be distinguished from the others in the phylogenic trees developed based on the data obtained by single barcode gene. In addition, a phylogenic tree based only on plastid information (trnH-psbA + rbcL + matK) and another created on the data resulting from both nuclear and plastid genomes (trnH-psbA + rbcL + matK + ITS) was also generated. In general, ITS sequence, indicating high resolution at the genus and species level, appeared as the best barcode sequence of the present study. Phylogenic analysis demonstrated the genetic relationship between crop saffron and wild Crocus species. According to the results of this study, among 13 available sample, the wild species are Crocus cancellatus L. and Crocus sp. Eslamabad were hypothesized as the closest species to the Iranian saffron. The present investigation also indicated that the different ecotypes of C. sativus L. may have evolved through independent events probably due to geographic and environmental pressures.